Models for Natural Killer Cell Repertoire Formation. Issue 2 (2003) - Salmon-Divon, Mali; Höglund, Petter; Mehr, Ramit
Abstract : Natural killer (NK) cells lyse only cells that do not express sufficient levels of self class I MHC molecules. Inhibition of lysis is mediated by inhibitory receptors expressed by NK cells, such as the murine Ly49 receptors, that bind to MHC class I molecules. Since inhibitory receptor genes and MHC class I genes are located on different chromosomes, and are hence not automatically co-inherited, NK cells apparently adapt to the MHC environment during their development. Two models have been proposed to account for this "education" process of NK cells. The two-step selection model postulates that developing NK cells initiate the stable expression of a random set of Ly49 genes, and then undergo two selection steps, one for cells that express a sufficient number of self-MHC receptors, and one against cells that express too many inhibitory receptors. The sequential model postulates that a cell keeps initiating the stable expression of additional inhibitory receptors until a sufficient expression level of self-MHC specific receptors is reached, and the cell matures. In this study we implement both models in computer simulations, and compare simulation results to experimental data, in order to evaluate the relative plausibility of the two models.